Synthesis of N2‐Aryl‐2′‐Deoxyguanosine Modified Phosphoramidites and Oligonucleotides. Issue 1 (1st August 2019) - Ghodke, Pratibha P.; Pradeepkumar, P. I.
Abstract: The N 2 ‐position of 2′‐deoxyguanosine ( N 2 ‐position in dG) is well known for forming carcinogenic minor groove DNA adducts, which originate from environmental pollutants, chemicals, and tobacco smoke. The N 2 ‐dG DNA adducts have strong implications on biological processes such as DNA replication and repair and may, therefore, result in genomic instability by generating mutations or even cell death. It is crucial to know the role of DNA polymerases when they encounter the N 2 ‐dG damaged site in DNA. To get detailed insights on the in vitro DNA damage tolerance or bypass mechanism, there is a need to synthetically access N 2 ‐dG damaged DNAs. This article describes a detailed protocol of the synthesis of N 2 ‐aryl‐dG modified nucleotides using the Buchwald‐Hartwig reaction as a main step and incorporation of the modified nucleotides into DNA. In Basic Protocol 1, we focused on the synthesis of five different N 2 ‐dG modified phosphoramidites with varying bulkiness (benzyl to pyrenyl). Basic Protocol 2 describes the details of synthesizing N 2 ‐dG modified oligonucleotides employing the standard solid phase synthesis protocol. This strategy provides robust synthetic access to various modifications at the N 2 ‐position of dG; the modified dGs serve as good substrates to study translesion synthesis and repair pathways. Overall data presented in this article are based on earlier published reports. © 2019 by John Wiley & Sons, Inc.